A YSZ-based hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode, a preparation method and applications thereof
Patent Information
- Application Number
- CN202611121896.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-13
AI Technical Summary
然而,纯La2Ce2O7作为敏感电极材料存在电子导电性极差的关键缺陷,严重限制了硫化氢在三相界面处发生电化学氧化反应时的电荷转移速率,直接影响传感器的灵敏度和响应恢复速度
[0024](1)传感器利用的固体电解质为YSZ(8%mol Y2O3掺杂的ZrO2)固体电解质材料,具有良好的热稳定性和化学稳定性,可在高温及含硫腐蚀性气氛等复杂环境中实现硫化氢的可靠检测;
Smart Images

Figure CN122901286A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas sensor technology, specifically relating to a YSZ-based hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode, its preparation method, and its application in sewer gas detection. Background Technology
[0002] Hydrogen sulfide (H2S) is a colorless, highly toxic, and flammable acidic gas with a typical rotten egg odor. Hydrogen sulfide poses a significant health hazard; studies have shown that a concentration of 1.4 mg / m³... 3 Hydrogen sulfide can be detected at concentrations as low as 0.1 ppm, and even low concentrations can cause local irritation and neurological symptoms. High concentrations can be fatal to humans. Hydrogen sulfide is a major product of the anaerobic decomposition of organic matter in oxygen-deficient environments such as urban sewers, wastewater treatment facilities, and swamps.
[0003] Hybrid potential sensors based on yttrium-stabilized zirconia (YSZ) solid electrolytes are well-suited for detecting hydrogen sulfide in harsh environments due to their excellent high-temperature thermal stability, chemical durability, and resistance to sulfur poisoning. Significant progress has been made in the research of hybrid potential hydrogen sulfide sensors based on YSZ solid electrolytes in recent years. However, maintaining a low detection limit while further shortening the response / recovery time, improving long-term stability and moisture resistance, and conducting practical application research remain key challenges in this field.
[0004] The sensing performance of YSZ-based hybrid potentiometric sensors essentially depends on the physicochemical properties of the sensitive electrode material and its electrochemical reactivity at the electrode / electrolyte / gas three-phase interface. Among numerous candidate materials, La₂Ce₂O₇ shows potential as a hydrogen sulfide sensitive electrode material due to its unique defective fluorite structure. However, pure La₂Ce₂O₇ suffers from a critical defect of extremely poor electronic conductivity, severely limiting the charge transfer rate during the electrochemical oxidation reaction of hydrogen sulfide at the three-phase interface, directly affecting the sensor's sensitivity and response recovery speed. Furthermore, pure La₂Ce₂O₇ lacks specific adsorption and catalytic active sites for hydrogen sulfide, which is detrimental to achieving high-selectivity detection. Summary of the Invention
[0005] The purpose of this invention is to provide a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode, its preparation method, and its application in sewer gas detection.
[0006] Research has found that introducing transition metal elements at the B site in La₂Ce₂O₇ can effectively improve its electronic conductivity and enhance its electrocatalytic activity for hydrogen sulfide, showing great potential in terms of the overall performance of the sensitive electrode. This invention aims to improve key performance characteristics of the sensor, such as the detection limit, response recovery speed, and moisture resistance, promoting its practical application in real-time monitoring of low-concentration hydrogen sulfide. The hydrogen sulfide sensor involved is a hybrid potential type constructed using commercially available YSZ solid electrolyte as the ion-conducting layer and La₂CeNiO₇ material prepared by the citric acid complex sol-gel method as the sensitive electrode. In the La₂CeNiO₇ sensitive electrode material, the introduction of Ni significantly improves the material's electronic conductivity and electrocatalytic activity, and the sensor exhibits unique moisture resistance. This sensor can achieve rapid detection of ppb-level hydrogen sulfide and has successfully captured the daily variation of hydrogen sulfide concentration and abnormal fluctuations caused by water outages in sewage gas monitoring, fully demonstrating its reliability and application potential in real-world environments.
[0007] The present invention discloses a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode. From bottom to top, it comprises an alumina plate with an "M"-shaped Pt heater on its upper surface, a YSZ solid electrolyte substrate prepared on the upper surface of the "M"-shaped Pt heater and the alumina plate, a reference electrode prepared on one side of the upper surface of the solid electrolyte substrate, and a sensitive electrode prepared on the other side of the upper surface of the solid electrolyte substrate. The active material of the sensitive electrode is a La2CeNiO7 sensitive electrode material prepared by the citric acid complexation sol-gel method, and its preparation steps are as follows:
[0008] (1) Weigh out lanthanum nitrate hexahydrate, cerium nitrate hexahydrate and nickel nitrate hexahydrate according to the stoichiometric ratio, dissolve them in deionized water, stir to form a homogeneous solution, and then weigh out citric acid and add it to the homogeneous solution.
[0009] (2) Stir the mixed solution obtained in step (1) until it is uniform, and then stir it in a water bath at 70~90℃ to form a gel. Then dry the gel at 90~120℃ for 10~14h to obtain the precursor material.
[0010] (3) Grind the precursor material obtained in step (2) into a uniform powder of 100~300 mesh, and calcine it in steps to obtain the La2CeNiO7 sensitive electrode material.
[0011] Further, in step (1), 4.5~5.5 mmol of lanthanum nitrate hexahydrate, 2~3 mmol of cerium nitrate hexahydrate and 2~3 mmol of nickel nitrate hexahydrate are weighed and dissolved in 15~30 mL of deionized water and stirred into a homogeneous solution. Then, 14~16 mmol of citric acid is weighed and added to the homogeneous solution.
[0012] In step (3), the stepwise calcination is carried out in a muffle furnace at a heating rate of 3~7℃ / min to 300~350℃ for 1.5~2.5h, and then at the same heating rate to 900~1000℃ for 1.5~2.5h.
[0013] The present invention discloses a method for preparing a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode, the steps of which are as follows:
[0014] (1) Preparation of Pt reference electrode: Pt electrode is coated on both ends of the surface of YSZ solid electrolyte substrate with Pt paste. Then, two Pt wires with a length of 1.2~2cm are selected and folded into a "V" shape. Pt paste is then used to attach them to the center of the Pt electrode as electrode leads. At the same time, two Pt wires with a length of 0.8~1.2cm are attached to both ends of the "M" shaped Pt heater as heater leads. Finally, the obtained YSZ solid electrolyte substrate and alumina plate are sintered.
[0015] (2) Preparation of La2CeNiO7 sensitive electrode: The La2CeNiO7 sensitive electrode material is mixed with deionized water at a mass ratio of 1:0.5~2, and then ground thoroughly to form a slurry. The slurry is then coated onto the Pt electrode at one end of the upper surface of the YSZ solid electrolyte substrate to form a strip-shaped sensitive electrode with a thickness of 0.05~0.15mm, and then sintered.
[0016] (3) Mix alumina powder and deionized water at a mass ratio of 1:0.5~2 to form a paste, and coat it on the Pt electrode at the other end of the upper surface of the YSZ solid electrolyte substrate to form a reference electrode with a thickness of 0.1~0.3 mm; use an inorganic adhesive to tightly bond the lower surface of the YSZ solid electrolyte substrate to the upper surface of the alumina plate, and then bake it under an infrared lamp to make the various parts of the sensor firmly bonded.
[0017] (4) The electrode leads and heater leads are soldered to a six-pin socket and aged to obtain the YSZ-based hydrogen sulfide sensor based on the La2CeNiO7 sensitive electrode described in this invention.
[0018] Further, in step (1), the obtained YSZ solid electrolyte substrate and alumina plate are placed in a muffle furnace and sintered at 900~1000℃ for 20~40min to solidify the Pt connection points and remove organic matter in the Pt slurry. The heating rate during sintering is 3~7℃ / min.
[0019] In step (2), the material is placed in a muffle furnace and sintered at 900~1000℃ for 1.5~2.5h, with a heating rate of 3~7℃ / min during sintering;
[0020] In step (2), water glass (Na2SiO3·9H2O) and alumina powder are mixed evenly at a volume ratio of 2~4:1 to obtain an inorganic binder;
[0021] In step (4), the heater lead is connected to a DC linear power supply, and the output current is adjusted to 250~300mA so that the sensor is continuously powered on and aged in the air atmosphere for 60~80 hours.
[0022] The YSZ-based hybrid potential-type hydrogen sulfide sensor based on the La2CeNiO7 sensitive electrode prepared by this invention can be applied in sewer gas detection.
[0023] The YSZ-based hybrid potential-type hydrogen sulfide sensor based on the La2CeNiO7 sensitive electrode described in this invention has the following advantages:
[0024] (1) The solid electrolyte used by the sensor is YSZ (8%mol Y2O3 doped ZrO2) solid electrolyte material, which has good thermal and chemical stability and can reliably detect hydrogen sulfide in complex environments such as high temperature and sulfur-containing corrosive atmosphere.
[0025] (2) La2CeNiO7 was prepared as a sensor sensitive electrode by citric acid complex sol-gel method. The preparation method is simple, the raw materials are inexpensive, and the reproducibility is low.
[0026] (3) By selecting La2Ce2O7 with excellent intrinsic properties as the matrix material and introducing Ni element at its B site for substitution modification, the electronic conductivity and electrocatalytic activity of the sensitive electrode are effectively improved, thereby significantly reducing the detection limit of the sensor and greatly accelerating the response and recovery speed. In addition, the sensor has unique anti-humidity properties and good selectivity. It can still maintain high response and strong anti-interference ability in harsh environments such as high temperature and high humidity, and has strong practicality. Attached Figure Description
[0027] Figure 1 : A schematic diagram of the structure of the YSZ-based hybrid potential-type hydrogen sulfide sensor of the present invention;
[0028] like Figure 1 As shown, the names of each part are: Pt reference electrode 1, La2CeNiO7 sensitive electrode 2, YSZ solid electrolyte substrate 3, and alumina plate with an "M"-shaped Pt heater on the upper surface 4.
[0029] Figure 2 XRD patterns of pure La2Ce2O7 and materials incorporating Ni, Mn and Fe elements in this invention (horizontal axis represents angle, vertical axis represents intensity);
[0030] like Figure 2 As shown, the diffraction peaks of pure La2Ce2O7 are consistent with the standard card, indicating that it has a pure cubic defect fluorite structure. After the introduction of Ni, Mn, and Fe, the main peaks all shift to higher angles, proving that the dopant ions have been successfully integrated into the lattice. The appearance of impurity peaks indicates that some dopants in the three materials are precipitated in the form of LaNiO3, LaMnO3, and LaFeO3 second phases, respectively.
[0031] Figure 3 SEM images of several sensitive electrode materials described in this invention at different magnifications, wherein (a) and (e) correspond to La2Ce2O7, (b) and (f) correspond to La2CeNiO7, (c) and (g) correspond to La2CeMnO7, and (d) and (h) correspond to La2CeFeO7;
[0032] like Figure 3 As shown, the La2CeNiO7 material has fine particles and exhibits a loose and porous structure. This porous structure can provide more active sites, which is beneficial for gas catalysis. At the same time, it can promote the diffusion of gas molecules, accelerate the adsorption of hydrogen sulfide gas and the desorption of reaction products, and effectively shorten the response and recovery time of the sensor.
[0033] Figure 4 The response and recovery curves (Figure a) and response and recovery time histograms (Figure b) of the various sensors described in this invention for 200ppb and 500ppb H2S at an operating temperature of 550℃ are shown respectively. Sensors S1 to S4 are hydrogen sulfide sensors based on La2Ce2O7, La2CeNiO7, La2CeMnO7 and La2CeFeO7 sensitive electrode materials, respectively.
[0034] like Figure 4 As shown, sensor S2, based on La2CeNiO7 material, exhibits the highest response value, with response values of −59.5 mV and −90.6 mV for 200 ppb and 500 ppb H2S, respectively; it also has the fastest response / recovery speed, with response and recovery times of 5 s and 12 s for 500 ppb H2S, respectively. The response and recovery times of sensors S1~S4 for 200 ppb and 500 ppb H2S are shown in Table 1.
[0035] Table 1: Response and recovery time data of sensors S1~S4 to 200ppb and 500ppb H2S
[0036]
[0037] Figure 5The sensor based on La2CeNiO7 material in this invention exhibits the response-recovery curves (Figure a) of H2S in the concentration range of 5ppb~1000ppb at 550℃, and the relationship between the response value and the logarithm of the H2S concentration (Figure b); a comparison of the sensor's response values to various gases at different concentrations (Figure c); and the response-recovery curves of the sensor to 200ppb H2S under different humidity conditions (Figure d).
[0038] like Figure 5 As shown in (a) and (b), the sensor exhibits a sensitive and reversible response to H2S, with the response value monotonically increasing with increasing H2S concentration. It can reliably detect H2S as low as 5 ppb, demonstrating a low detection limit. The sensor's sensitivity exhibits piecewise linear characteristics, with sensitivities of −18.76 mV / decade in the concentration ranges of 5–50 ppb and −78.86 mV / decade in the concentration ranges of 5–1000 ppb. Figure 5 As shown in (c), the sensor's response to H2S is much higher than that to gases such as NO2, SO2, CO, and CH4, demonstrating excellent selectivity. Figure 5 As shown in (d), the sensor exhibits the characteristic that the response value increases with increasing humidity. At a humidity of 60%RH, the sensor's response value changes very little, with a change rate of only −4.2%, indicating good moisture resistance.
[0039] Figure 6 The sensor based on La2CeNiO7 material in this invention detected the change in H2S concentration in sewer gas over a week (Figure a) and the effect curve of a sudden water outage event on the hydrogen sulfide concentration in sewer gas (Figure b).
[0040] like Figure 6 As shown, the sensor successfully captured the daily variation pattern of H2S concentration in sewer gas monitoring. That is, on normal working days and under normal conditions (excluding factors such as water outages, Day 1 corresponds to Friday, and Day 4 corresponds to Monday), the concentration of H2S in the sewer is higher in the morning than in the afternoon. At the same time, it accurately recorded the abnormally low concentration of H2S in the sewer on Monday (Day 4 in Figure a) due to reduced human activity on Sunday, as well as the delayed abnormal fluctuation of H2S concentration caused by sudden water outages.
[0041] The unusually low concentration on Monday was due to reduced activity in the laboratory building on Sunday, resulting in insufficient H2S accumulation overnight. On Monday morning, wastewater flow had not yet returned to normal levels, leading to a lack of sufficient overnight gas accumulation. As normal activities resumed during the day on Monday, wastewater discharge gradually increased. By the afternoon, the input of organic matter and water flow disturbance jointly promoted the generation and release of H2S, causing the afternoon concentration to be higher than in the morning.
[0042] like Figure 6 As shown in b, the H2S concentration initially decreased, then increased, and then decreased again after the unexpected water outage and subsequent resumption of water supply. This was mainly attributed to the combined effect of delayed microbial metabolism and hydraulic transport. During the water outage, the organic load and sulfate supply were interrupted, inhibiting the metabolic activity of sulfate-reducing bacteria. In the initial stage of water supply resumption, gas production capacity was at a low level, hence the initial significant decrease in concentration. As water use resumed, wastewater continued to flow in the pipeline. The high-concentration sulfur-containing wastewater accumulated upstream took several hours to reach the monitoring point, leading to a compensatory increase in concentration in the afternoon. Finally, the accumulated gas in the pipeline was gradually diluted and flushed out by the normal water flow, and the concentration gradually returned to normal levels. Detailed Implementation
[0043] Example 1: Fabrication of a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensing electrode
[0044] This embodiment provides a YSZ-based hybrid potential H2S sensor with La2CeNiO7 as the sensitive electrode material and its preparation method. The specific steps are as follows:
[0045] (1) Preparation of La2CeNiO7 sensitive electrode material: Weigh 5 mmol of lanthanum nitrate hexahydrate, 2.5 mmol of cerium nitrate hexahydrate and 2.5 mmol of nickel nitrate hexahydrate and dissolve them in 20 mL of deionized water and stir to form a uniform solution. Then weigh 15 mmol of citric acid and add it to the uniform solution and stir. After stirring the mixed solution evenly, place it in a water bath at 80 °C and stir to form a gel. Then dry the gel at 100 °C for 12 h to obtain the precursor material. Grind the precursor material into a uniform powder of about 200 mesh and calcine it in a muffle furnace at a heating rate of 5 °C / min to 320 °C for 2 h and then calcine it at 950 °C for 2 h to obtain the La2CeNiO7 sensitive electrode material.
[0046] (2) Making the sensor:
[0047] Preparation of Pt reference electrodes: Pt electrodes were coated on both ends of the surface of the YSZ solid electrolyte substrate using Pt paste. Two 1.5cm long Pt wires were then folded into a "V" shape and bonded to the center of the Pt electrodes with Pt paste as electrode leads. At the same time, two 1.0cm long Pt wires were bonded to both ends of an "M" shaped Pt heater as heater leads. Finally, the obtained YSZ solid electrolyte substrate and alumina plate were placed in a muffle furnace and sintered at 1000℃ for 30min (heating rate 5℃ / min) to solidify the Pt junctions and remove organic matter from the Pt paste.
[0048] Preparation of La2CeNiO7 Sensing Electrode: La2CeNiO7 sensing electrode material was mixed with deionized water at a mass ratio of 1:1, thoroughly ground to form a slurry, and then coated onto the Pt electrode at one end of the upper surface of the YSZ solid electrolyte substrate to form a 0.1 mm thick strip-shaped sensing electrode. This was then sintered in a muffle furnace at 950℃ for 2 h (heating rate 5℃ / min). Alumina powder was mixed with deionized water at a mass ratio of 1:1 to form a paste, which was then coated onto the Pt electrode at the other end of the upper surface of the YSZ solid electrolyte substrate to form a 0.2 mm thick reference electrode. Then, water glass (Na2Si) was used... To obtain an inorganic binder, O3·9H2O) and alumina powder are mixed uniformly at a volume ratio of 3:1. The lower surface of the obtained YSZ solid electrolyte substrate is then tightly bonded to the upper surface of the alumina substrate using this binder. The substrate is then baked under an infrared lamp for 2 hours to ensure a stable bond between the various parts of the sensor. The electrode leads and heater leads are soldered to a six-pin socket. The heater leads of the sensor are then connected to a DC linear power supply, and the output current is adjusted to 280mA. The sensor is then continuously powered on and aged in laboratory air for 3 days to obtain the YSZ-based hydrogen sulfide sensor based on the La2CeNiO7 sensitive electrode described in this invention.
[0049] Comparative Example 1: Fabrication of a YSZ-based hybrid potentiometric hydrogen sulfide sensor based on a La2Ce2O7 sensing electrode
[0050] This comparative example provides a YSZ-based mixed potential H2S sensor with pure La2Ce2O7 as the sensitive electrode material and its preparation method. The only difference from Example 1 is that in step (1), nickel nitrate hexahydrate is not added, but 5 mmol of lanthanum nitrate hexahydrate and 5 mmol of cerium nitrate hexahydrate are weighed out. The rest of the preparation conditions are exactly the same as in Example 1.
[0051] Comparative Example 2: Fabrication of a YSZ-based hybrid potentiometric hydrogen sulfide sensor based on a La2CeMnO7 sensing electrode
[0052] This comparative example provides a YSZ-based mixed potential H2S sensor with La2CeMnO7 as the sensitive electrode material and its preparation method. The only difference from Example 1 is that in step (1), 2.5 mmol nickel nitrate hexahydrate is replaced with 2.5 mmol manganese acetate tetrahydrate, and the rest of the preparation conditions are exactly the same as in Example 1.
[0053] Comparative Example 3: Fabrication of a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeFeO7 sensitive electrode
[0054] This comparative example provides a YSZ-based mixed potential H2S sensor with La2CeFeO7 as the sensitive electrode material and its preparation method. The only difference from Example 1 is that in step (1), 2.5 mmol nickel nitrate hexahydrate is replaced with 2.5 mmol ferric nitrate nonahydrate, and the rest of the preparation conditions are exactly the same as in Example 1.
[0055] The four sensors prepared in Example 1 and Comparative Examples 1-3 were placed in a static testing system for H2S gas-sensing performance testing. The operating temperature of the sensors was controlled by adjusting the supply current of the Pt heater using a DC linear power supply, and the test temperature was set to 550℃. The sensor response value ΔV was defined as the difference between the steady-state voltage signal (Vgas) between the sensing electrode and the reference electrode in H2S atmosphere and the baseline voltage signal (Vair) between the sensing electrode and the reference electrode in air, i.e., ΔV = Vgas − Vair. The response time (τ) 90 The recovery time (τ) is defined as the time required for the sensor's output signal to change from the baseline after exposure to H2S until the response value reaches 90% of the total response value (ΔV). 90 The response signal is defined as the time required for the sensor to recover from steady state after being removed from the H2S until the response value drops to 10% of the total response value (ΔV).
[0056] During testing, the sensor was first placed in a gas collecting bottle filled with laboratory air. Once the output signal stabilized, the baseline voltage Vair was recorded. Simultaneously, a certain volume of H2S standard gas was drawn using a syringe and injected into another gas collecting bottle of the same specifications. This gas was then diluted with laboratory air and thoroughly shaken to prepare the required concentration of H2S test gas. The sensor was then quickly transferred to the gas collecting bottle containing the H2S test gas, and Vgas was recorded once the response signal reached a steady state. After the test, the sensor was returned to the air bottle to allow the signal to return to the baseline. Selectivity and humidity resistance tests followed the same static testing method, with the gas type and humidity conditions adjusted according to the specific requirements of each test item.
[0057] The application verification method of the sensor prepared in Example 1 in sewer gas monitoring is as follows: The H2S concentration in the sewer well of a certain experimental building was continuously monitored at fixed points for 7 days using a gas sampling method, with sampling and testing conducted daily at 9:00 and 15:00. During sampling, a rubber tube was inserted approximately 1.2m into the well, and the gas was extracted into an aluminum foil sampling bag using an air pump. After returning to the laboratory, a static gas mixing method was used; a 1L test bottle was rinsed three times with the target gas before being filled with the target gas and immediately used for testing.
[0058] Test results show that the sensor successfully captured the diurnal variation pattern of H2S concentration in sewer gas monitoring. Specifically, on normal working days and under normal conditions (excluding factors such as water outages), the concentration is higher in the morning than in the afternoon. Within the monitoring period, the sensor also accurately recorded abnormally low concentrations on Mondays due to reduced human activity on Sundays, as well as delayed abnormal fluctuations in H2S concentration caused by sudden water outages. These results fully demonstrate the reliability and application potential of this sensor for real-time monitoring of low-concentration H2S in practical environments.
Claims
1. A YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode, comprising, from bottom to top, an alumina plate with an "M"-shaped Pt heater on its upper surface, a YSZ solid electrolyte substrate prepared on the upper surface of the "M"-shaped Pt heater and the alumina plate, a reference electrode prepared on one side of the upper surface of the solid electrolyte substrate, and a sensitive electrode prepared on the other side of the upper surface of the solid electrolyte substrate, characterized in that: The active material of the sensitive electrode is a La2CeNiO7 sensitive electrode material prepared by the citric acid complexation sol-gel method, and its preparation steps are as follows. (1) Weigh out lanthanum nitrate hexahydrate, cerium nitrate hexahydrate and nickel nitrate hexahydrate according to the stoichiometric ratio, dissolve them in deionized water, stir to form a homogeneous solution, and then weigh out citric acid and add it to the homogeneous solution. (2) Stir the mixed solution obtained in step (1) until it is uniform, and then stir it in a water bath at 70~90℃ to form a gel. Then dry the gel at 90~120℃ for 10~14h to obtain the precursor material. (3) Grind the precursor material obtained in step (2) into a uniform powder of 100~300 mesh, and calcine it in steps to obtain the La2CeNiO7 sensitive electrode material.
2. The YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode as described in claim 1, characterized in that: In step (1), 4.5-5.5 mmol of lanthanum nitrate hexahydrate, 2-3 mmol of cerium nitrate hexahydrate and 2-3 mmol of nickel nitrate hexahydrate are weighed and dissolved in 15-30 mL of deionized water and stirred into a homogeneous solution. Then, 14-16 mmol of citric acid is weighed and added to the homogeneous solution.
3. The YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode as described in claim 1, characterized in that: In step (3), the stepwise calcination is carried out in a muffle furnace at a heating rate of 3~7℃ / min to 300~350℃ for 1.5~2.5h, and then at the same heating rate to 900~1000℃ for 1.5~2.5h.
4. A method for preparing a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode, as described in any one of claims 1 to 3, comprising the following steps: (1) Preparation of Pt reference electrode: Pt electrode is coated on both ends of the upper surface of YSZ solid electrolyte substrate with Pt paste. Then, two Pt wires with a length of 1.2~2cm are selected and folded into "V" shape. Pt paste is then used to attach them to the center of the Pt electrode as electrode leads. At the same time, two Pt wires with a length of 0.8~1.2cm are attached to both ends of "M" shaped Pt heater as heater leads. Finally, the obtained YSZ solid electrolyte substrate and alumina plate are sintered. (2) Preparation of La2CeNiO7 sensitive electrode: The La2CeNiO7 sensitive electrode material is mixed with deionized water at a mass ratio of 1:0.5~2, and then ground thoroughly to form a slurry. The slurry is then coated onto the Pt electrode at one end of the upper surface of the YSZ solid electrolyte substrate to form a strip-shaped sensitive electrode with a thickness of 0.05~0.15mm, and then sintered. (3) Mix alumina powder and deionized water at a mass ratio of 1:0.5~2 to form a paste, and coat it on the Pt electrode at the other end of the upper surface of the YSZ solid electrolyte substrate to form a reference electrode with a thickness of 0.1~0.3 mm; use an inorganic adhesive to tightly bond the lower surface of the YSZ solid electrolyte substrate to the upper surface of the alumina plate, and then bake it under an infrared lamp to make the various parts of the sensor firmly bonded. (4) The electrode leads and heater leads are soldered to a six-pin socket and aged to obtain the YSZ-based hydrogen sulfide sensor based on the La2CeNiO7 sensitive electrode described in this invention.
5. The method for preparing a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode as described in claim 4, characterized in that: In step (1), the obtained YSZ solid electrolyte substrate and alumina plate are placed in a muffle furnace and sintered at 900~1000℃ for 20~40min to solidify the Pt connection points and remove organic matter in the Pt slurry. The heating rate during sintering is 3~7℃ / min.
6. The method for preparing a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode as described in claim 4, characterized in that: In step (2), the sample is placed in a muffle furnace and sintered at 900~1000℃ for 1.5~2.5h, with a heating rate of 3~7℃ / min during sintering.
7. The method for preparing a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode as described in claim 4, characterized in that: In step (3), water glass and alumina powder are mixed evenly at a volume ratio of 2 to 4:1 to obtain an inorganic binder.
8. The method for preparing a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode as described in claim 4, characterized in that: In step (4), the heater lead is connected to a DC linear power supply, and the output current is adjusted to 250~300mA so that the sensor is continuously powered on and aged in the air atmosphere for 60~80 hours.
9. The application of a YSZ-based hybrid potential-type hydrogen sulfide sensor based on a La2CeNiO7 sensitive electrode as described in any one of claims 1 to 3 in the detection of gases in sewers.